2013
DOI: 10.5114/pdia.2013.33379
|View full text |Cite
|
Sign up to set email alerts
|

Total skin electron irradiation techniques: a review

Abstract: Total skin electron irradiation (TSEI) has been employed as one of the methods of mycosis fungoides treatment since the mid-twentieth century. In order to improve the effects and limit the complications following radiotherapy, a number of varieties of the TSEI method, frequently differing in the implementation mode have been developed. The paper provides a systematic review of the different varieties of TSEI. The discussed differences concerned especially: (i) technological requirements and geometric condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…Total skin electron irradiation (TSEI) is one of the most effective treatments of malignant skin diseases, such as mycosis fungoides (MF) and cutaneous lymphomas 1 , 2 , 3 , 4 The goal is to treat the entire body surface to a limited depth with a relatively uniform dose (e.g., ±10%) (5) . In order to deliver the treatment dose at a shallow depth, low‐energy electrons are considered for TSEI, which is commonly performed with a 6 MeV beam.…”
Section: Introductionmentioning
confidence: 99%
“…Total skin electron irradiation (TSEI) is one of the most effective treatments of malignant skin diseases, such as mycosis fungoides (MF) and cutaneous lymphomas 1 , 2 , 3 , 4 The goal is to treat the entire body surface to a limited depth with a relatively uniform dose (e.g., ±10%) (5) . In order to deliver the treatment dose at a shallow depth, low‐energy electrons are considered for TSEI, which is commonly performed with a 6 MeV beam.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective reviews (n = 41-180) from recent decades have demonstrated the efficacy of high-dose (≥30 Gy) TSEI in achieving high clinical response rates (1, 4-9). The vast majority of these studies used the large-field/modified Stanford technique, in which the skin surface is irradiated in a discontinuous manner, with the patient changing position six times by 60° during one treatment fraction (10). In contrast, a rotational TSEI technique (RTSEI), in which a patient is automatically rotated at a constant speed about the vertical axis while being irradiated with single or dual fields, allowing for continuous treatment delivery, has been previously described (11).…”
Section: Introductionmentioning
confidence: 99%
“…TSEBT is an example of treatment, that may be applied in such cases (8). The dose is delivered using one of various radiation techniques, with six dual field, rotational, and rotary dual techniques among the most common examples (9).…”
Section: Discussionmentioning
confidence: 99%